High dose rate interstitial brachytherapy for early stage lip cancer using customized dental spacer. (8th April 2020) - Masui, Koji; Yamazaki, Hideya; Suzuki, Gen; Shimizu, Daisuke; Kawabata, Kanako; Noguchi, Naoki; Takenaka, Tadashi; Yoshida, Ken; Murakami, Naoya; Naito, Masayuki; Yamamoto, Toshiro; Kanamura, Narisato; et al.
Abstract: The present study aimed to report the efficacy and toxicity of our high-dose-rate (HDR) brachytherapy for early stage lip cancer (LC) using customized dental spacers. A retrospective analysis was performed among six patients with early stage LC treated with HDR interstitial brachytherapy between April 2015 and August 2019 using customized dental spacers. The total treatment dose was 49 Gy/7 fractions or 54 Gy/9 fractions. The median follow-up duration for the patients was 13 (range: 2–52) months. All patients completed the entire brachytherapy protocol safely and have experienced no local recurrence thus far. The CTV D100 and D90 values per fraction were median 100 (range: 98.3–100) % prescribed dose (PD) and median 133.4 (range: 129.3–138.9) % PD, respectively. The D2cc and D0.1cc values per fraction for the mandible were median 1.07 (range, 0.79–1.88) Gy and median 1.65 (range: 1.21–2.83) Gy, D2cc and D0.1cc values per fraction for oral cavity were median 1.48 (range, 1.31–1.72) Gy and median 2.73 (range: 1.79–2.88) Gy, respectively. Acute toxicities encountered were mucositis and lip edema limited to the irradiated area; none of them was beyond grade 2 and all were resolved within 1–2 months after treatment. We did not observe any late grade 2 adverse events or worse. This study shows that the adverse effects of HDR brachytherapy for early stage LC can be minimized using a dental spacer. Cooperation with the dentistry department is essential to make spacers that are individually customized for each patient.